Performance evaluation of open-graded friction course (OGFC) for high-strength application - Yee, Wan Rong (Nanyang Technological University, 2022)
In Singapore, 12% of our land are utilised for land transportation so it is important that our roads have good drainage ability to minimise flooding since the rainfall could get quite heavy on certain periods of the year. There are numerous roads in close proximity to housing estates. The noise produced by vehicles on the roads can often be a noise pollution to the residences alongside roads. Open-graded friction course (OGFC) is a type of porous asphalt mixture (PAM), where-by it is stronger than high-voids PAM as the voids-in-total mix (VTM) in OGFC is at moderate level (up to 15% VTM) and is lesser than high-voids PAM. OGFC brings about various benefits such as reduced noise level from tyre-road interactions and also better handles drainage as compared to dense mix that is widely used in Singapore highways. A study was undertaken to evaluate several mixes with moderate VTM such as OGFC and similar mixes for their potential application in high-strength pavement such as expressways in Singapore. Three design gradation were examined, with one OGFC from LTA standards at 7-9% VTM, and two other gradations at 14-15% VTM (one being coarser, one being finer, in terms of aggregate representation by size). The asphalt binder used was PG76 grade. The optimal binder content was first determined. Drain- down test and Cantabro test were conducted to get the range of feasible optimal binder content for respective gradation. A common optimal binder content at 6% was determined and used for the rest of the evaluation. Performance tests were then conducted, such as- Marshall stability test, Moisture susceptibility test, Dynamic creep test, Ravelling test and Clogging test. From Marshall stability test results, all three gradations had acceptable stability for OGFC. The best gradation was then deduced from each test supported with data and results. The coarser gradation at 14-15% is found to have the best performance. This gradation performed the best in moisture susceptibility test with a high percentage of 98.25% of retained moisture susceptibility and revelling test with the lowest average percentage loss of 1.26%. It had also decent results for testes such as creep test where it appeared to be better than expected, and for the other tests such as clogging, and Marshall stability test it was of better results as compared to other similar gradations. Herein, it is feasible to use a moderately porous asphalt mix in high-strength pavement application for our highways.